Decision Support System for Determination of Promotion Using Simple Additive Weighting - Ahmad Hafidzul Kahfi; Mochammad Rizky Kusumayudha; Ahmad Fachrurozi (Institute of Computer Science (IOCS), 2021)
The human resources of a company greatly influence many aspects that determine the success of the work of the company. One of the most important processes in the human resources department of a company or business entity is the promotion process. When determining which employees are eligible for promotion, it is difficult for companies to make a decision. This is because many employees are highly qualified and the number of positions required is limited. In addition, the processing of employee evaluation data in companies is still done manually, so that considering a large number of employees, the possibility of input errors is quite high and takes a relatively long time. For that, we need a decision support system that can assist companies in selecting employees to be promoted to various positions. The method used is the Simple Additive Weighting method, which starts from finding problems, determining goals, determining standards and alternatives, determining weights until the final result is obtained, then carrying out a ranking process, which will select the alternatives given so that employees who deserve to be promoted can be determined.